P–701 Fresh vs frozen PGT-A cycles in donor oocyte recipients. (6th August 2021) - Castillo, J C; Guerrero, J; Ten, J; Martinez, M; Llacer, J; Bernabeu, A; Bernabeu, R
Abstract: Study question: For donor oocyte recipients, are clinical outcomes superior for fresh versus frozen euploid embryos? Summary answer: Among donor oocyte recipients receiving euploid embryos, fresh embryos are associated with superior clinical outcomes when compared with frozen embryos. What is known already: A recent large retrospective cohort national registry study reported that among donor oocyte recipients, fresh embryos were associated with better clinical outcomes when compared with frozen embryos. This finding contrast with data from autologous oocytes. Since embryo quality at embryo transfer (ET) may introduce a significant confounder, the additional analysis of recipients receiving only euploid embryos may add important information on the subject. Study design, size, duration: Retrospective cohort analysis of PGT-A IVF-cycles of women using donor oocytes resulting in fresh blastocyst ET compared to the first frozen blastocyst ET from freeze-all cycles between 2014 and 2020 at Instituto Bernabeu, Alicante, Spain. A total of 349 donor oocyte cycles were analyzed, in which 211 were fresh and 138 were frozen ETs. Thawed oocytes were not excluded. Participants/materials, setting, methods: Clinical pregnancy (gestational sac plus embryo heart beating at 6–7 weeks), was the primary outcome measure. Secondary outcomes included pregnancy and early pregnancy loss rate. aCGH platform tested the embryos transferred in fresh whereas either aCGH or NGS platforms were used for embryos submitted to elective frozen cycles. Vitrification was used as cryopreservation technique. Fresh transfers were performed in artificial cycles. Different types of endometrial preparations were used for FET in the study. Main results and the role of chance: Recipients in the fresh group were significantly younger and had more embryos transferred compared to the frozen group (41.3 vs 42.5 and 1.2 vs 1.1, respectively). More clinical pregnancies were observed in the fresh compared to the frozen group (108/211 versus 54/138, respectively, odds ratio (ODR) 1.63 [95% CI 1.05–2.52]; p = 0.02). Pregnancy rates were also higher in the fresh compared to the frozen group (128/211 versus 63/138, respectively, odds ratio (ODR) 1.83 [95% CI 1.18–2.83]; p = 0.005). Early pregnancy losses were similar in both groups (p = 0.2). Limitations, reasons for caution: Implantation failure and abnormal male tests were the most frequent indications for PGT-A. Because of the observational nature of the results in this limited sample size, a cause–effect relationship should not be assumed; evidence from larger well-designed randomized control trials is still required before clinical advice can be suggested. Wider implications of the findings: When PGT-A analysis is deemed to be necessary in oocyte recipients, cryopreservation may have an adverse impact on IVF outcomes. Future studies exploring ET in natural vs artificial cycles are warranted to further isolate the impact of vitrification and the uterine environment on IVF outcomes. Trial registration number: Not applicable